The Effect of Aerial Bombardment on Insurgent Civilian Victimization. (27th May 2021) - Tucker, Colin
Abstract: Little is known about how air strikes influence insurgent behavior toward civilians. This study provides evidence that air strikes against the Islamic State of Iraq and Syria (ISIS) by counterinsurgency forces were a contributing factor in its civilian victimization. I theorize that air strikes expanded the distribution of insurgent fatalities to include higher-echelon membership and, at the same time, imposed psychological impairments on its fighters. As a consequence, these changes relaxed restraints on civilian abuse at the organizational and individual levels. This theory is informed by interviews of ISIS defectors and translations of ISIS documents and tested through a statistical analysis of granular-level data on air strikes and one-sided violence during ISIS's insurgency. These findings contribute to our knowledge of insurgent behavior and provide important policy implications in the use of air strikes as a counterinsurgency (COIN) tool.